METODE PEMBELAJARAN TGT DENGAN BERMAIN ULAR TANGGA (UTANG) UNTUK MENINGKATKAN HASIL BELAJAR PPKNMATERI PELANGGARAN HAM PADA SISWA KELAS X SMA NEGERI 1 SEMARANG TAHUN PELAJARAN 2013/2014 - Dargito, Dargito (Forum Ilmu Sosial, 2014)
This study aims to determine the significant differences in Citizenship learning result among students who were taught with TGT learning model by snakes and ladders games versus the students taught conventionally in first grade students at SMA Negeri 1 Semarang in academic year 2013/2014. This study was action research class. The population in this study was the first grade students of SMA Negeri 1 Semarang, with 470 students. The sample in this study were 39 students, which consisted was X MIA 2 students of SMA Negeri 1 Semarang. Data collection was done by the testing method. At the first cycle, the brave of students increase 15,22 %. The mean of activity those are not relevant decrease at the second cycle at 12.01%. The score of students in material Human Rights is good. It proves that the application of TGT learning model by snakes and ladder games make the influence of Citizenship learning result of the fisrt grade students of SMA Negeri 1 Semarang in academic year 2013/2014.